The Isoperla of California (Plecoptera: Perlodidae); Updated Male Descriptions and Adult Keys for 18 Western Nearctic Species - Sandberg, John B. (Illiesia, 2013)
The adults of 18 western Nearctic species of the stonefly genus Isoperla Banks from California, Colorado, Oregon, Washington and Utah were studied. Updated species keys and male descriptions are presented. Three species occurring in adjacent states but not recorded in California, I. rainiera Jewett, I. tilasqua Szczytko & Stewart and I. umpqua Szczytko & Stewart, are included in the descriptions and keys.
Keywords: entomology; Isoperla; Perlodidae; Plecoptera; United States of America; USA; adult species key; western Nearctic